2013
DOI: 10.1111/cdev.12199
|View full text |Cite
|
Sign up to set email alerts
|

Judging Words by Their Covers and the Company They Keep: Probabilistic Cues Support Word Learning

Abstract: Statistical learning may be central to lexical and grammatical development: The phonological and distributional properties of words provide probabilistic cues to their grammatical and semantic properties. Infants can capitalize on probabilistic cues to learn grammatical patterns in listening tasks. However, infants often struggle to learn labels when performance requires attending to less obvious cues, raising the question of whether probabilistic cues support word learning. The current experiment presented fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 52 publications
(54 reference statements)
5
47
0
1
Order By: Relevance
“…Our hypothesis was supported: Children experienced greater difficulty and showed wider variability in comprehending passives and object RCs, and performance on these structures was significantly and independently predicted by their SL ability. The data are consistent with previous demonstrations of a significant SL–grammar link in acquisition (Conway et al., ; Kidd, ; Lany, ; Lum et al., ), and extend those data by demonstrating that the link is related to the frequency distributions of specific structures. Conway et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our hypothesis was supported: Children experienced greater difficulty and showed wider variability in comprehending passives and object RCs, and performance on these structures was significantly and independently predicted by their SL ability. The data are consistent with previous demonstrations of a significant SL–grammar link in acquisition (Conway et al., ; Kidd, ; Lany, ; Lum et al., ), and extend those data by demonstrating that the link is related to the frequency distributions of specific structures. Conway et al.…”
Section: Discussionsupporting
confidence: 91%
“…Associations between SL and grammar have been reported using both auditory and visual SL tasks (e.g., in children: Lany, 2014;Kidd, 2012;in adults: Conway et al, 2010;Misyak et al, 2010), suggesting that a domain-general capacity for SL supports acquisition and processing. We chose a nonlinguistic visual test of SL that has been shown to elicit variability in children (Arciuli & Simpson, 2011) and has revealed a link between SL and language proficiency (Arciuli & Simpson, 2012).…”
mentioning
confidence: 99%
“…Similarly, another study found that adult implicit learning performance as measured by the Serial Reaction Time Task was correlated with the performance on two foreign language examinations (Kaufman et al, 2010). Another relevant study explored infants learning of form-based categories when statistical cues (i.e., distributional and phonological cues about label identity) were probabilistically predictive of semantic category membership (i.e., whether the label tended to be paired with animals or vehicles; Lany, 2014). Only the infants in the study with higher levels of grammatical development were able to use the statistical cues to support learning mappings between the labels and semantic categories, which is consistent with the idea that infants' sensitivity to relations between forms and meanings supports both learning of words and grammar.…”
Section: Article In Pressmentioning
confidence: 99%
“…A first line of behavioral AGL research emerged from the landmark study by Saffran et al (1996), showing that eight-month-old infants utilize transitional probabilities of syllables for defining word boundaries in continuous speech. Follow-up studies demonstrated that infants employ statistical speech properties in word segmentation (Marchetto & Bonatti, 2015;Saffran, 2001;Shukla et al, 2011), discovering non-adjacent structure regularities (Gómez & Maye, 2005;Marchetto & Bonatti, 2015), acquiring lexical-semantic categories (Lany, 2014;Lany & Saffran, 2010), and establishing grammatical categories (Höhle et al, 2004;Shi et al, 2006). A second line of behavioral AGL research is based on the seminal study by Marcus et al (1999), reporting seven-month-old infants' ability to detect abstract speech patterns, as defined by repetitions and alternations of speech elements (see also Gómez & Gerken, 1999).…”
Section: Agl Research In Infancymentioning
confidence: 99%